IFRS 9 e o reconhecimento das receitas de uma carteira de crédito consignado gerado fora da rede de agências: Um Estudo no Banco do Estado do Rio Grande do Sul S/A - Silva, Juliana Costa da (Universidade do Vale do Rio dos Sinos, 2019)
This study aimed to determine the impact on accounting of credit operation revenues by introducing IFRS 9 in a payroll loan portfolio generated outside the BANRISUL branch network. To determine this impact, an explanatory, documentary and qualitative research was developed, that comprised the Unit of Microcredit and Special Business located in the General Direction of the referred bank. Compared to previous studies based on simulated data and data from this research, which are based on an active credit portfolio, there is a difference between the research findings. When compared to studies that verified the comparison between the local GAAPs and the IFRS 9 standard, it was found that there was a difference in the recognition of the revenue from credit operations and the expense of provision for operations in previous studies. In this study, it is included that the implementation of IFRS 9 has an impact on the recognition of the revenue of the credit operations of the portfolio researched, since the increase of the appropriate revenue in IFRS 9 in the observed period. With regard to the recognition of the provision for loss of credit, IFRS 9 didn’t generate an impact, since the Brazilian banking market is highly regulated and already carries out the provision of credit losses based on the risk of the operation and the client for many years, and as effectively as IFRS 9 standard.
Keywords: BACEN GAAP; IFRS 9; Receita; Operação de crédito; Empréstimo; BACEN GAAP; IFRS 9; Revenue; Credit operation; Loan; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis